Explaining cross-cultural service interactions in tourism with Shenkar’s Cultural Friction - Cheok, Jason *; Aleti, T; Hede, A. M. (Routledge Open Select, 2015)
In this paper, we commence a new dialogue on cross-cultural research in tourism. Using Shenkar’s (2001) metaphor of cultural friction as the analytical framework, we examine crosscultural service interactions between guests and service-providers in a luxury hotel. Cultural friction departs from, and extends, the notion of ‘cultural distance’, as it recognises asymmetry in social-economic conditions and considers the goals and the influence of control and power between the interacting parties. We use the Critical Incident Technique and Narrative Inquiry as the data collection technique and analytical approach respectively. The findings reveal that guests and service-providers use a number of strategies to exert power and gain control during their interactions, including subjective essentialism and stereotyping, to achieve their goals. The implications for tourism and hospitality management include providing cross-cultural sensitivity training to service-providers, ensuring a cultural-diverse employee composition, and to foster cross-cultural understanding amongst employees. We further suggest to develop strategies to facilitate effective cross-cultural service interactions based on evidence about cultural norms, expectations and behaviours from specific cultural groups. Further research is recommended to connect specific interactions between the interacting parties to examine whether the various strategies used leads to effective cross-cultural communication.